Comparative Studies of Resveratrol, Oxyresveratrol and Dihydrooxyresveratrol on Doxorubicin-Treated Lung Cancer Cells - Waraporn Yahayo; Veerachai Pongkittiphan; Roogntawan Supabphol; Somrudee Saiyudthong (My University, 2024)
Objectives: This research aims to comparatively investigate the capability of resveratrol (RES) and RES analogues, oxyresveratrol (Oxy-RES) and dihydrooxyresveratrol (DHoxy-RES), to potentiate doxorubicin (DOX) effects against lung carcinoma epithelial cells. Methods: All experiments were performed on lung carcinoma cell lines (A549) with DOX combination between DOX and RES or RES analogues. Cell viability or growth inhibitory effect was assessed by MTT assay and genes associated with survival and metastasis were monitored by real-time polymerase chain reaction (RT-PCR). Results: DOX obviously demonstrated cytotoxic and anti-metastatic activities against A549 cells. Expression of gene-associated with both activities was potentiated by RES and RES analogues. Oxy-RES showed highest capability to potentiate DOX effects. DHoxy-RES showed nearly no effect to DOX activities. Conclusions: These results provided an important basis of DOX combination with RES analogues, especially Oxy-RES, for better therapeutic effect. Further studies in human should be performed on exploring combination of DOX and Oxy-RES.
Keywords: MTT assay; Viability assay; Sirtuins and Resveratrol in Medicine